The future role of livestock in feeding the world - Herrero, Mario (2011)
Today's global population of 7 billion is predicted to expand to more than 9 billion by 2050. Will that more crowded world be able to produce enough food for everyone? And should livestock be part of evolving food security plans? In this 26 minute seminar, Mario Herrero, agro-ecological systems analyst at the International Livestock Research Institute (ILRI) says that “the future lies in what we do with the world’s resources”, and concludes “livestock science will be fundamental to deliver the solutions that the world needs.”